Progress in gene editing tools, implications and success in plants: a review - Bhuyan, Suman Jyoti; Kumar, Manoj; Ramrao Devde, Pandurang; Rai, Avinash Chandra; Mishra, Amit Kumar; Singh, Prashant Kumar; Siddique, Kadambot H. M. (Frontiers in Genome Editing, 2023)
Genetic modifications are made through diverse mutagenesis techniques for crop improvement programs. Among these mutagenesis tools, the traditional methods involve chemical and radiation-induced mutagenesis, resulting in off-target and unintended mutations in the genome. However, recent advances have introduced site-directed nucleases (SDNs) for gene editing, significantly reducing off-target changes in the genome compared to induced mutagenesis and naturally occurring mutations in breeding populations. SDNs have revolutionized genetic engineering, enabling precise gene editing in recent decades. One widely used method, homology-directed repair (HDR), has been effective for accurate base substitution and gene alterations in some plant species. However, its application has been limited due to the inefficiency of HDR in plant cells and the prevalence of the error-prone repair pathway known as non-homologous end joining (NHEJ). The discovery of CRISPR-Cas has been a game-changer in this field. This system induces mutations by creating double-strand breaks (DSBs) in the genome and repairing them through associated repair pathways like NHEJ. As a result, the CRISPR-Cas system has been extensively used to transform plants for gene function analysis and to enhance desirable traits. Researchers have made significant progress in genetic engineering in recent years, particularly in understanding the CRISPR-Cas mechanism. This has led to various CRISPR-Cas variants, including CRISPR-Cas13, CRISPR interference, CRISPR activation, base editors, primes editors, and CRASPASE, a new CRISPR-Cas system for genetic engineering that cleaves proteins. Moreover, gene editing technologies like the prime editor and base editor approaches offer excellent opportunities for plant genome engineering. These cutting-edge tools have opened up new avenues for rapidly manipulating plant genomes. This review article provides a comprehensive overview of the current state of plant genetic engineering, focusing on recently developed tools for gene alteration and their potential applications in plant research.